Ectopic Pregnancy as Previable Delivery - Buskmiller, Cara (Christian bioethics, 2024)
Inside and outside of a Christian worldview, bioethicists have discussed ectopic pregnancy at some length as a maternal-fetal vital conflict. Most bioethicists agree that methotrexate and salpingostomy are low-risk, successful interventions for this life-threatening pathology, and are thus beneficent, just, and wholly acceptable. A small cohort of Christian, largely Catholic, bioethicists have reservations about methotrexate and salpingostomy, but cannot resolve their internal disputes about these because of flawed casuistry. This paper aims to settle the issue about whether methotrexate and salpingostomy are acceptable within a Catholic worldview: despite the best arguments in favor of methotrexate as a moral option, it is morally unacceptable, and despite hesitation about salpingostomy related to analogies with previable delivery, it is the optimal procedure for ectopic pregnancy.